Pengamanan Lontar Digital Dengan Tanda Tangan Digital Menggunakan Algoritma RSA - Harta, I Gede Bendesa Aria; Gede Suhartana, I Ketut; Anom Cahyadi, I Gusti Ngurah; Pramartha, Cokorda; Ari Mogi, I Komang; Agung Raharja, Made (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
Lontar is a relic of cultural heritage whose basic source of manufacture is from rontal or tal leaves containing evidence of all records of aspects of ancient historical life which include historical values, religion, philosophy, medicine, literature and other sciences so that their sustainability needs to be maintained. Security of digital lontar will make it easier to preserve a lontar work so that it is not changed or falsified by irresponsible parties, where digital lontar in PDF format will be given a digital signature to maintain the authenticity of the document. Documents that are signed will be difficult for other parties to change, if the contents of a digital ejection are changed it will cause the digital signature to change. Based on the research conducted, from the results of testing the security of digital ejection with digital signatures using the RSA algorithm, the test results from RMSE (Root Mean Square Error) for description results with an average of 69.7794143. The larger or random the description results, the more complex the description results will be.